Arcade of humanism: cognitive science of Professor A. V. Sokolov’s creativity and the symmetry «library – humanism» (root makroproblems, or how many things a person can accommodate) - A. V. Kumanova (Библиосфера, 2013)
In the mirror of the cognitological approach professor A. V. Sokolov’s creative career as a humanist, possessing the knowledge of informatics, social communication and information society is shown. The author reveals his contribution to the formation of the status of library and bibliographical studies as scientific and practical fields within information and communication cycle of knowledge. The methodological impact of his book «Library and Humanism: Mission of the Library in the global technogenic civilization» as a synthesis of the humanitarian-scientific and natural-scientific knowledge in the technogenic civilization is revealed.